Tensions in the Marketplace: Reflections on the Major Recording Companies Documentation of Jazz in the late 1990s and New Millennium Years - Nicholson, Stuart (Jazz Research Journal, 2005)
The survival of jazz has to be seen in the context of today’s increasingly complex infrastructure of profitmaximizing multinationals whose homogenizing tendencies are at odds with the music’s inherent complexity. Jazz no longer has the kind of mass market appeal that is attractive to the majors so in order for the music to survive in a niche market where audiences appreciate instrumental creativity, it has to evolve beyond the jazz tradition and embrace the kind of radical processes of evolution which musical forms undergo. Unless contemporary musicians move beyond the paradigm of traditional orthodoxies they could well, by most definitions at least, be participating in something that is closer to a folk form rather than an art form - interesting to witness live, but, as the 1990s return to the certainties of hard bop demonstrated, when the music is in competition with the past, the past will always win because the original artists are seen to be the source of ‘authenticity.’ When music - or any art form - becomes a refuge from the present, from facing up to the world today, then its force is diminished; it becomes an embalmed corpse, beautiful to behold but ultimately inert.